TOTAL FENOL DAN AKTIVITAS ANTIOKSIDAN DARI SONNERATIA ALBA BARK - Herawati, Netti (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2012)
DOWNLOAD PDFThe aim of this research was to examine the total phenolic content and radical scavenging capacity related to antioxidant potential in different fractions of methanolic extract of mangroves trees, Sonneratia alba bark. Total phenolic content was determined by the Folin-Ciocalteau method. Antioxidant potential has been determined as the free radical scavenging ability using a stable radical, diphenyl-picryl-hydrazyl (DPPH). Three fractions of methanol extracts of S. alba were subjected to free radical scavenging activity in order to evaluate their antioxidant activity. The free radical scavenging activity of different fractions obtained from successive fractionation of methanol extracts with organic solvents of different polarities; hexane, chloroform, and ethyl acetate. Total phenolics content of three fraction and crude extract are 17.84 ±0.974, 156.310 ±0.703, 226.89 ±0.605, 249.56 ±0942 (GAE ?g/g) respectively for hexane, chloroform, ethyl acetate, and crude extracts (methanol extract). Antioxidant assay showed that the ethyl acetate and chloroform fractions have the high activity with IC50 10.27 ?g/ml and 27.34 ?g/ml, respectively, while a weak activity was showed by hexane fraction with 147 ?g/ml. Linear correlation between the total antioxidant capacity of the fractions and the total phenolic contents was observed (r2=0.918). This data indicated that the antioxidant activity mainly due to phenolic compound contain in those fraction. The results indicate promising S.alba or the utilization as significant source of natural antioxidant. Key words: Sonneratia alba, total phenolics, radical scavenging activity, antioxidant, DPPH